Self-presentation strategies and their determinants - Valionienė, Aistė (Psichologija, 1998)
The issue that is to be discussed in this paper is the phenomenon of “self-presentation”, which refers to the process by which individuals attempt to control the impressions others form of them. Since the impressions people make on others have implications for how others perceive, evaluate and treat them, as well as for their own views of themselves, people sometimes behave in ways that will create certain impressions in others’ eyes. Four main self-presentation strategies can be distinguished. Each of them determines the character and direction of the interpersonal relationships in different ways. The choice of the particular self-presentation strategy and the degree to which individuals are motivated to control how others perceive them are affected by a number of situational, external, and dispositional variables. The aim of the discussion on self-presentation strategies and their determinants presented in this article is to provide coherence to the literature in the area and supply a framework for empirical research regarding self-presentation.